Is Social Security Really Bad For Growth? - Giorgio Bellettini; Carlotta Berti Ceroni (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1995)
This paper develops a model of endogenous growth with overlapping generations to investigate the joint determination of social security, public investment and growth in a small open economy. We argue that a pure pay-as-you-go system provides the taxpayers with the incentives to support growth-oriented policies, which increase the future productivity of labor. We find that outcomes characterized by positive levels of intergenerational redistribution, public investment and long run growth can be sustained as subgame-perfect Nash equilibria of an infinitely repeated intergenerational game, if and only if the marginal productivity of public capital is large enough. Furthermore, we show that transfers either comove with public investment and growth or display a non-monotonic relation, where they initially increase along with public investment and growth and then decrease.
Keywords: 330